Analysis of the characteristics of lower limb muscle synergy controlistic patterns during unilateral load-bearing walking - Jinwei ZHAO; Luyao CHEN; Fuyong LIU; Piotr ASCHENBRENNER; Tomasz GRZYWACZ; Jan STRAWIŃSKI (Baltic Journal of Health and Physical Activity, 2025)
Background: This study aims to investigate how unilateral load-bearing conditions influence lower limb muscle synergistic control patterns during walking. Understanding these patterns is crucial for elucidating the biomechanics of gait under loaded conditions. Materials and Methods: Sixteen healthy adults participated in the study. The Qualisys 600 series motion capture system was used to collect kinematic data, and the Delsys 16-channel wireless surface EMG system to record muscle activity. Four unilateral loading conditions (LL10, LR10, LL20, LR20) were tested, with normal walking as the control. Results: Load-bearing conditions significantly altered muscle contributions in different synergistic units. For example, in Synergistic Unit 1, the vastus medialis (VM) became more dominant during load-bearing walking compared to normal walking, where the vastus lateralis (VL) and tibialis anterior (TA) were primary. The soleus (SOL) also played a significant role during left-sided load-bearing at 20% body weight. Loading significantly affected the contribution weights of SOL in Synergistic Unit 2 and the semimembranosus (SM) in Synergistic Unit 4. Conclusions: Unilateral loading conditions significantly change lower limb muscle synergistic control patterns, primarily through shifts in muscle contributions. These changes may reflect the increased demand for stability and balance during load-bearing walking, providing insights into the human walking mechanism under loaded conditions.